2020
DOI: 10.1002/trc2.12027
|View full text |Cite
|
Sign up to set email alerts
|

Shared mechanisms for cognitive impairment and physical frailty: A model for complex systems

Abstract: Introduction We describe findings from a large study that provide empirical support for the emerging construct of cognitive frailty and put forth a theoretical framework that may advance the future study of complex aging conditions. While cognitive impairment and physical frailty have long been studied as separate constructs, recent studies suggest they share common etiologies. We aimed to create a population predictive model to gain an understanding of the underlying biological mechanisms for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
(66 reference statements)
2
29
0
Order By: Relevance
“…Among 5076 subjects screened for reversible cognitive frailty, the prevalence of reversible cognitive frailty was shown to be 19.9% (n = 1008), with older age, female, higher education and marital status (single) shown to be associated with reversible cognitive frailty. 46 The model of "potentially reversible" cognitive frailty has been investigated in population-based studies, 29,[50][51][52][53][54][55][56][57][58] in a memory clinic population, 59 and in a case-control study, 60 as well as in populations included in randomized control trials, [61][62][63] where the prevalence of "potentially reversible" cognitive frailty ranges from 6.3% to 59.1%. Most of the studies that focused on the "potentially reversible" cognitive frailty model used the modified CHS criteria, with a few studies shown to use the FRAIL scale 46,55,56 or Edmonton Frailty Scale 60 to assess physical frailty.…”
Section: Reversible/potentially Reversible Cognitive Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…Among 5076 subjects screened for reversible cognitive frailty, the prevalence of reversible cognitive frailty was shown to be 19.9% (n = 1008), with older age, female, higher education and marital status (single) shown to be associated with reversible cognitive frailty. 46 The model of "potentially reversible" cognitive frailty has been investigated in population-based studies, 29,[50][51][52][53][54][55][56][57][58] in a memory clinic population, 59 and in a case-control study, 60 as well as in populations included in randomized control trials, [61][62][63] where the prevalence of "potentially reversible" cognitive frailty ranges from 6.3% to 59.1%. Most of the studies that focused on the "potentially reversible" cognitive frailty model used the modified CHS criteria, with a few studies shown to use the FRAIL scale 46,55,56 or Edmonton Frailty Scale 60 to assess physical frailty.…”
Section: Reversible/potentially Reversible Cognitive Frailtymentioning
confidence: 99%
“…16 In another study, omics analysis with machine learning statistical approaches suggested that cognitive frailty is driven by multisystem dysfunction across multiple cellular processes, including genetic alterations, nutrient and lipid metabolism, and elevated levels of circulating proinflammatory proteins. 54…”
Section: Othersmentioning
confidence: 99%
“…Considering that lipids are a major component (70%) of the composition of the human brain, variations in these compounds could potentially be used as biomarkers of cognitive problems. In recent research, Sargent et al ( 2020 ) found that low levels of vitamin E alpha tocopherol, omega-6 and 3 and albumin were associated with CF. In addition, these researchers observed a second pattern of association characterized by a low level of trans fats, as indicated by measuring low and high density lipoproteins (LDL and HDL).…”
Section: Role Of Biomarkersmentioning
confidence: 99%
“…In addition, based on data from the Canadian Study of Health and Aging, Song et al (2014) found that the incidence rate of cognitive impairment increased exponentially with the increase of frailty index, and frailty is an independent risk factor for cognitive impairment. Cognitive impairment is related to frailty, and both have common biological mechanisms, including genetic alternations, immune system dysfunction, and neuroinflammation (Sargent et al, 2020).…”
Section: Relationship Between Cognitive Function and Frailtymentioning
confidence: 99%